Control of avocado root rot caused by Phytophthora cinnamomi with different Trichoderma strains at Chavimochic Irrigation Project - Gastañadui, Paul (2021)
Avocado root rot caused by Phytophthora cinnamomi is one of the main problems affecting avocado (Persea americana) cultivation in Peru, especially at the Chavimochic Irrigation Project. The objective of this study was to evaluate the effect of different Trichoderma strains on the control of Phytophthora cinnamomi in Zutano rootstock under greenhouse conditions. Five isolates of Trichoderma were tested: Trichoderma sp. (Chav01); Trichoderma harzianum (Chavo2); Trichoderma harzianum (UNALM01); Trichoderma viride (UNALM02); and a commercial strain of Trichoderma sp. Evaluations were performed at 30, 45, and 60 days. All isolates colonized the rhizosphere of the avocado. No relation was found between the formation of more Trichoderma colonies and Phytophthora improved control. All strains controlled the root rot, but Chav01 and Chav02 showed the greatest diameter of stem, dry matter in the root, and percentage of healthy root in comparison with UNALM01, UNALM02, and the commercial strain. Thus, the native isolates of Trichoderma from the Chavimochic area can be added to the list of potential new Trichoderma species to control Phytophthora cinnamomi.